Electropolymerization of robust conjugated microporous polymer membranes for rapid solvent transport and narrow molecular sieving - Zhou, Zongyao; Li, Xiang; Guo, Dong; Shinde, Digambar B.; Lu, Dongwei; Chen, Long; Liu, Xiaowei; Cao, Li; Aboalsaud, Ammar M.; Hu, Yunxia; Lai, Zhiping (Nature communications, 2020)
Pore size uniformity is one of the most critical parameters in determining membrane separation performance. Recently, a novel type of conjugated microporous polymers (CMPs) has shown uniform pore size and high porosity. However, their brittle nature has prevented them from preparing robust membranes. Inspired by the skin-core architecture of spider silk that offers both high strength and high ductility, herein we report an electropolymerization process to prepare a CMP membrane from a rigid carbazole monomer, 2,2’,7,7’-tetra(carbazol-9-yl)-9,9’-spirobifluorene, inside a robust carbon nanotube scaffold. The obtained membranes showed superior mechanical strength and ductility, high surface area, and uniform pore size of approximately 1 nm. The superfast solvent transport and excellent molecular sieving well surpass the performance of most reported polymer membranes. Our method makes it possible to use rigid CMPs membranes in pressure-driven membrane processes, providing potential applications for this important category of polymer materials. Conjugated microporous polymers (CMPs) have great potential in membrane applications but are often brittle. Here, the authors develop an electropolymerization process to form a skin-core architecture which allows them to overcome mechanical limitations while keeping the excellent separation performance of CMP membranes.